9‐Fluorenone‐2‐Carboxylic Acid as a Scaffold for Tubulin Interacting Compounds. Issue 7 (13th May 2013) - Calogero, Francesco; Borrelli, Stella; Speciale, Gaetano; Christodoulou, Michael S.; Cartelli, Daniele; Ballinari, Dario; Sola, Francesco; Albanese, Clara; Ciavolella, Antonella; Passarella, Daniele; Cappelletti, Graziella; Pieraccini, Stefano; et al.
Abstract The introduction of a hydrophobic group at position 7 of 9‐fluorenone‐2‐carboxylic acid generates new tubulin binders, the design of which is suggested by modeling studies. The synthesis is based on the use of 2, 7‐dibromo‐fluorenone as starting material. The antiproliferative activity on two different cell lines, fluorescent microscopy, flow cytometry, and sedimentation assay tests confirmed the supposed mechanism.